PERTANGGUNGJAWABAN PIDANA PENCEMARAN LINGKUNGAN HIDUP YANG DILAKUKAN OLEH KORPORASI - Muhari Agus Santoso (University of Merdeka Malang, 2016)
Research on criminal liability of environmental pollution by corporations, multinational corporations have shown a massive accumulation of wealth and created a wide range of personalities. Whereas in the field of criminal law, which is heavily linked to accountability referred to in the Criminal Code (KUHP) only recognizes individuals as the subject of criminal law. Corporations not yet seen as a subject of criminal law. However, in subsequent developments, it is mentioned in the special criminal law. The relationship with vicarious liability or corporate liability in criminal law can be described as the imposition of criminal responsibility to a person in the capacity of the principal offender, based on the offense or at least an element of offense committed by another person. The person who acts, however, must be responsible only for his actions. It takes firmness to put the corporate criminal responsibility on the environmental offense so that the corporation that carries out negligence in exploiting nature causing pollution can be punished according to its fault. Similarly, socialization is needed to society about the possibility of environmental depictions that must be accounted by the corporation. It is so important to capture community participation in maintaining environmental wisdom.